2020
DOI: 10.7554/elife.55827
|View full text |Cite
|
Sign up to set email alerts
|

Time-dependent cytokine and chemokine changes in mouse cerebral cortex following a mild traumatic brain injury

Abstract: Traumatic brain injury (TBI) is a serious global health concern, many individuals live with TBI-related neurological dysfunction. A lack of biomarkers of TBI has impeded medication development. To identify new potential biomarkers, we time-dependently evaluated mouse brain tissue and neuronally derived plasma extracellular vesicles proteins in a mild model of TBI with parallels to concussive head injury. Mice (CD-1, 30–40 g) received a sham procedure or 30 g weight-drop, and were euthanized 8, 24, 48, 72, 96 h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
17
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(21 citation statements)
references
References 106 publications
0
17
0
Order By: Relevance
“…The goal of pre-clinical studies is to provide a spectrum of knowledge generated from multiple, distinct pre-clinical models that encompass the full range of injuries from mild to severe TBI (Katz & Molina, 2018;Mychasiuk et al, 2014;Shultz et al, 2017;Siebold et al, 2018). For example, a recent large-scale proteomic study of closed head weigh drop TBI in mice reveals distinct C/C protein dynamics compared to our study with no reported increase in IL-1β, IL-5, IL-6, TNFα, CXCL1, CXCL2, CXCL10, CCL2, or CCL3 PI (Tweedie et al, 2020). Indeed, IL-6 was chronically downregulated in this diffuse injury model highlighting the importance of generating data from multiple pre-clinical models of TBI.…”
Section: Con Clus Ionmentioning
confidence: 75%
“…The goal of pre-clinical studies is to provide a spectrum of knowledge generated from multiple, distinct pre-clinical models that encompass the full range of injuries from mild to severe TBI (Katz & Molina, 2018;Mychasiuk et al, 2014;Shultz et al, 2017;Siebold et al, 2018). For example, a recent large-scale proteomic study of closed head weigh drop TBI in mice reveals distinct C/C protein dynamics compared to our study with no reported increase in IL-1β, IL-5, IL-6, TNFα, CXCL1, CXCL2, CXCL10, CCL2, or CCL3 PI (Tweedie et al, 2020). Indeed, IL-6 was chronically downregulated in this diffuse injury model highlighting the importance of generating data from multiple pre-clinical models of TBI.…”
Section: Con Clus Ionmentioning
confidence: 75%
“…In previous studies NADPH oxidase activity increases within 1 h in neurons and a second increase is seen around 24–96 h after trauma. Interestingly, CCL5 mRNA is upregulated in the cortex immediately after injury and decreases 24–48 h after brain trauma which is parallel to elevated OS in brain tissue [ 10 , 11 , 23 ]. Many studies have shown the correlation between CCL5 and the NADPH oxidase response in immune cells' priming processes [ 24 ]; moreover NADPH oxidase is associated with CCL5 activation [ 25 ].…”
Section: Discussionmentioning
confidence: 99%
“…Increasing our understanding of the circadian and immune system response to injury can help to elucidate the complex outcomes of TBI and may shed light on more innovative treatments. For example, recent work in inflammation has found mouse cortical cytokines and chemokines show temporal expression pattern changes from as soon as 8 h following a single closed head injury to as long as 30 days post post-TBI ( Tweedie et al, 2020 ). Further characterization of the specific impairments to the circadian system can also advance understanding of TBI outcomes and help to better inform treatment.…”
Section: Discussionmentioning
confidence: 99%